2012
DOI: 10.1088/0034-4885/75/4/046401
|View full text |Cite
|
Sign up to set email alerts
|

Few-body physics with ultracold atomic and molecular systems in traps

Abstract: Few-body physics has played a prominent role in atomic, molecular and nuclear physics since the early days of quantum mechanics. It is now possible-thanks to tremendous progress in cooling, trapping and manipulating ultracold samples-to experimentally study few-body phenomena in trapped atomic and molecular systems with unprecedented control. This review summarizes recent studies of few-body phenomena in trapped atomic and molecular gases, with an emphasis on small trapped systems. We start by introducing the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
253
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(267 citation statements)
references
References 341 publications
(909 reference statements)
9
253
0
1
Order By: Relevance
“…Apart from a few exceptions [34][35][36][37][38][39][40][41], it has commonly been assumed that particles of different kinds have the same mass and the main impact on properties of the system comes from an imbalance of the number of particles. However, recently it was shown that for particles confined in a harmonic trap, the mass difference between different fermionic components leads to their spatial separation if interactions are strong enough [42].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from a few exceptions [34][35][36][37][38][39][40][41], it has commonly been assumed that particles of different kinds have the same mass and the main impact on properties of the system comes from an imbalance of the number of particles. However, recently it was shown that for particles confined in a harmonic trap, the mass difference between different fermionic components leads to their spatial separation if interactions are strong enough [42].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we instead fit the full three-dimensional energies E 3d 2,1 /( ω ρ ) to a power series in g 1d . The fit yields the same linear coefficient as the perturbative treatment of H 1d and a slightly more negative coefficient for the quadratic term, −0.120754251 (1), where the number in round brackets denotes the uncertainty of the fit (the uncertainty of the three-dimensional energies is negligible for this analysis).…”
Section: Resultsmentioning
confidence: 84%
“…Ultracold few-atom systems provide clean model systems in which the system parameters such as the interaction strength and confinement geometry can be controlled with high accuracy [1][2][3][4]. Recently, twocomponent Fermi gases consisting of lithium atoms in two different hyperfine states have been prepared and probed experimentally in highly elongated, nearly harmonic external traps with an aspect ratio η around ten [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…While the properties of unitary Fermi systems with zero-range interactions are fully determined by the s-wave scattering length [12,14,[51][52][53][54] those of Bose systems additionally depend on a three-body parameter [15,17]. Specifically, if the two-body interactions are modeled by zero-range potentials, then a three-body regulator is needed to prevent the Thomas collapse of the N -boson (N ≥ 3) system [17,55].…”
Section: Three Dimensional Testsmentioning
confidence: 99%